2020
DOI: 10.14203/oseana.2020.vol.45no.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Teknik-Teknik Remediasi Sedimen Terkontaminasi Logam Berat

Abstract: Sediments are important in influencing changes and movements of the heavy metals in the aquatic environment. Heavy metals contamination of the sediments has negative ecological impacts on the environment. Therefore, economical, effective, and environmentally friendly remediation processes are needed. Purposes of the remediation are to reduce toxicity, bioavailability, and mobility of the metals from the polluted sediments. The remediations are developed using physical-chemical, biological and combination of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…Obtained results are highly affected by the geochemical properties of the site. Nevertheless, the heavy metals concentrations found in this study turned out to be comparable with values typically reported in the literature [60][61][62][63] 5, for the assessed heavy metals with a content value higher than the XRF minimum detectable concentration. The EF values were interpreted as described by [64], where EF < 2 indicates deficient to minimal enrichment; 2 ≤ EF < 5 moderate enrichment; 5 ≤ EF < 20 significant enrichment; 20 ≤ EF ≤ 40 high enrichment and EF > 40 indicates extremely high enrichment.…”
Section: Heavy Metals Analysissupporting
confidence: 90%
“…Obtained results are highly affected by the geochemical properties of the site. Nevertheless, the heavy metals concentrations found in this study turned out to be comparable with values typically reported in the literature [60][61][62][63] 5, for the assessed heavy metals with a content value higher than the XRF minimum detectable concentration. The EF values were interpreted as described by [64], where EF < 2 indicates deficient to minimal enrichment; 2 ≤ EF < 5 moderate enrichment; 5 ≤ EF < 20 significant enrichment; 20 ≤ EF ≤ 40 high enrichment and EF > 40 indicates extremely high enrichment.…”
Section: Heavy Metals Analysissupporting
confidence: 90%
“…Fitoremediasi ini menggunakan teknologi hemat biaya, efisien, dan ramah lingkungan yang berbasis pada tumbuhan penumpukan logam untuk menghilangkan logam beracun, termasuk radio nuklida, serta polutan organik dari tanah dan air yang terkontaminasi [11]. Tiga metode fitoremediasi utama dapat digunakan untuk mencapai efek detoksifikasi kontaminan dari lingkungan: fitoetraksi, stabilisasi, dan volatilisasi [12]. Tanaman yang memiliki kemampuan fitoremediasi dalam mengurangi timbal di dalam air dapat memberikan kontribusi penting untuk membersihkan lingkungan perairan yang terkontaminasi salah satu tanaman yang bagus dalam menetralisir logam timbal yaitu Tanaman Great Duckweed (Spirodela polyrhiza) dapat digunakan dalam fitoremediasi air yang terkontaminasi oleh logam berat, termasuk timbal.…”
Section: Hasil Dan Pembahasanunclassified
“…Heavy metals in the interstitial water of surface sediments move into the overlying water due to differences in the concentrat Additionally, heavy metals in ionic, organic-bound, and particulate forms may unde resuspension, mutual transformation, and precipitation processes during this process. linity in the intertidal zone varies significantly with the flowing of the fresh water tidal processes, and thus influences the solubility of the heavy metals [66].…”
Section: Mechanisms Of the Migration And Transformation Of Heavy Meta...mentioning
confidence: 99%